El Modelo Servqual y la satisfacción de la calidad del servicio en la dirección financiera del GADM de Echeandía Provincia Bolívar. - Torres Garcia, Andrea Elizabeth (2022)
The current research work called SERVQUAL model and the satisfaction of the quality service in the Financial Management at Echeandía municipality, located in Bolívar province, presents as a problem: How does the quality of Service affect the satisfactions of the user in the Financial Management at Echeandía municipality, Bolívar province for this reason, describes the dimensions on which the evaluation of the quality of the service and the satisfaction of the user is based through the use of the SERVQUAL model. For the investigation the survey was used in a sample of 286 people who use the Service of the hypothesis was carried out using the Kolmogorov Smirnov normality test that rejected the ho hypothesis, the Spearman correlation, was also used and the calculation and analysis op Cronbach Alpha results. It is concluded that user expectation are high. Regarding the perception, the answer by the majority of de respondents were little or not satisfactory showing de dissatisfaction with the service received.